Closed loop Fuzzy Logic Controlled Interleaved DC-to-DC converter Fed DC Drive System - Elavarasu, R; Christober Asir Rajan, C (International Journal of Engineering and Technology, 2018)
This paper deals with comparison of responses of PI and Fuzzy Logic controlled DC-to-DC converter Fed DC motor (FLCDDCDCM) systems. The DC input is converted into high frequency AC using full bridge inverter. The output is stepped up using a transformer and then it is rectified using voltage doubler rectifier. The open loop system with T filter at the output is simulated. The closed loop PI & FLC based DDCDCM systems are designed, modeled and simulated using Matlab/Simulink. The time domain parameters of FL controlled system are compared with those of PI controlled system. The results indicated that FL controlled DDCDCM system has better response than PI controlled DDCDCM system.Â